2013
DOI: 10.2337/db13-0022
|View full text |Cite
|
Sign up to set email alerts
|

Exaggerated Glucagon-Like Peptide 1 Response Is Important for Improved β-Cell Function and Glucose Tolerance After Roux-en-Y Gastric Bypass in Patients With Type 2 Diabetes

Abstract: β-Cell function improves in patients with type 2 diabetes in response to an oral glucose stimulus after Roux-en-Y gastric bypass (RYGB) surgery. This has been linked to the exaggerated secretion of glucagon-like peptide 1 (GLP-1), but causality has not been established. The aim of this study was to investigate the role of GLP-1 in improving β-cell function and glucose tolerance and regulating glucagon release after RYGB using exendin(9-39) (Ex-9), a GLP-1 receptor (GLP-1R)–specific antagonist. Nine patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
227
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(264 citation statements)
references
References 55 publications
32
227
2
3
Order By: Relevance
“…65 Postprandial GLP-1 secretion is substantially and durably increased early after RYGB, before significant weight loss has occurred, due to increased delivery of nutrients to the distal small intestine. 127 The importance of the incretin effect is unclear, with some studies showing that GLP-1 receptor blockade abolishes the RYGB-related improvement in beta-cell glucose sensitivity and insulin secretion 127 while another study found only minimal impairment in glucose tolerance following GLP-1 blockade after RYGB. 128 The durability of the effect of bariatric surgery on glycaemic control has been observed in the Swedish Obese Subjects Study; 72% of individuals with T2D achieved remission two years after surgery and 36% had maintained T2D remission 10 years after surgery.…”
Section: Bariatric Surgerymentioning
confidence: 99%
“…65 Postprandial GLP-1 secretion is substantially and durably increased early after RYGB, before significant weight loss has occurred, due to increased delivery of nutrients to the distal small intestine. 127 The importance of the incretin effect is unclear, with some studies showing that GLP-1 receptor blockade abolishes the RYGB-related improvement in beta-cell glucose sensitivity and insulin secretion 127 while another study found only minimal impairment in glucose tolerance following GLP-1 blockade after RYGB. 128 The durability of the effect of bariatric surgery on glycaemic control has been observed in the Swedish Obese Subjects Study; 72% of individuals with T2D achieved remission two years after surgery and 36% had maintained T2D remission 10 years after surgery.…”
Section: Bariatric Surgerymentioning
confidence: 99%
“…Exaggerated secretion of GLP-1 resulting in enhanced insulin secretion appears to be one of the important mechanisms underlying the resolution of diabetes often seen after gastric bypass surgery, as illustrated in experiments involving the GLP1R antagonist exendin 9-39, which eliminates the effect of the operation on insulin secretion and impairs glucose tolerance (77). The power of this mechanism is also illustrated by cases of reactive hypoglycemia after the operation, which may also be prevented by the antagonist (78), or by feeding through gastrostomy catheter, which eliminates the exaggerated GLP-1 response (79); the latter is in keeping with the principle that hypoglycemia results from extremely rapid carbohydrate entry into the small intestine (39).…”
Section: Gut Endocrine Regulation Of Glucose Metabolismmentioning
confidence: 99%
“…To identify the role of endogenous GLP-1 in the amelioration of impaired β-cell function after RYGBP, the specific GLP-1 receptor antagonist exendin 9-39 has been used in four cross sectional [48][49][50][51] studies and one short-term longitudinal 52 study in post-RYGBP patients. Exendin 9-39 completely blunts the recovery of β-cell glucose sensitivity (BCGS) 1 week and 3 months after RYGBP, 52 and worsens post-prandial glucose tolerance, although only minimally. 49 Exendin 9-39 suppresses insulin secretion in response to a meal by 50% 49,50 and corrects the profound reactive hypoglycemia in patients with severe neuroglycopenia.…”
Section: Antagonism Of Glp-1 Prevents the Improvement In β-Cell Functmentioning
confidence: 99%